Optimization of an indazole series of selective estrogen receptor degraders: Tumor regression in a tamoxifen-resistant breast cancer xenograft. Issue 22 (15th November 2015) - Govek, Steven P.; Nagasawa, Johnny Y.; Douglas, Karensa L.; Lai, Andiliy G.; Kahraman, Mehmet; Bonnefous, Celine; Aparicio, Anna M.; Darimont, Beatrice D.; Grillot, Katherine L.; Joseph, James D.; Kaufman, Joshua A.; Lee, Kyoung-Jin; et al.
Graphical abstract: Abstract: Selective estrogen receptor degraders (SERDs) have shown promise for the treatment of ER+ breast cancer. Disclosed herein is the continued optimization of our indazole series of SERDs. Exploration of ER degradation and antagonism in vitro followed by in vivo antagonism and oral exposure culminated in the discovery of indazoles47 and56, which induce tumor regression in a tamoxifen-resistant breast cancer xenograft.